Bounds for the Effective Shear Modulus - I. Ecsedi (Engineering Transactions, 2005)
This paper deals with the uniform torsion of nonhomogeneus elastic beams. The concept of the effective shear modulus is deduced from torsional rigidity. Upper and lower bounds are derived for the effective shear modulus. It is proven that the effective shear modulus of a compound beam is between the weighted arithmetic and harmonic means of shear moduli of the beam components.